(3GdahGcg GdOhGfi Ydi QSGdI GHf CHj RjO GdbjQhGfis - (3CMeO Zfje GdfaQGhis; (3CHh eMeO YHO Gddg Hf CHj RjO GdeGdcj GdbjQhGfj,J (B389 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3fGbUg GdChd hChd GdehLhO efg bhdg (B: (3JfHjgG ef GdChd GYde Cf JYQja GdSfI HeG aYdi Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hjbQC ai GdKGdKI HCe GdbQBf abW s
(3HgG fXGe GdJYbjHIs
(3fSNI eaccgs
(3hNWgG Objb s
(3heYfhfI HGdMHQ GdCMeQ s
(3hYdjgG JYdjbGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdeGdcjs